Experimental determination of activity interaction coefficients of components in Si-B-Fe and Si-B-Al ternary systems at 1723 K - Yang F.; Zhou Y.-Q.; Wu J.-J.; Ma W.-H.; Lei Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The interactions among impurity components in Si-based solution are the important thermodynamic parameters for the purification of silicon materials. A “same concentration” method was used to determine the activity interaction coefficients of Fe to B and Al to B in the silicon solution. Fe and Al were respectively dissolved into the binary Si-B solution at 1723 K with the holding time of 5 h, 7 h, 9 h, and 11 h. The equilibrium concentrations of Fe, B in the Si-B-Fe system and Al, B in the Si-B-Al system were determined. The interaction coefficients of Fe to B and Al to B were obtained by fitting the solubility data of B, Fe, and Al. The solubility relationships between B and [%Fe], and between B and [%Al] were obtained, respectively. It was found by the SEM and EPMA pictures of the samples that the third component Fe or Al added to the binary Si-B solution was alloyed, which verifies the accuracy of the experimental determination results. The significance of the activity interaction coefficient of B on boron removal from industrial silicon was analyzed.